PENGARUH MEDIA VISUAL MENGGUNAKAN APLIKASI LECTORA INSPIRE TERHADAP HASIL BELAJAR PESERTA DIDIK SISWA KELAS XI DI SMA ISLAM SUNAN GUNUNG JATI NGUNUT TAHUN PELAJARAN 2017/2018 - Ngubaidillah, Ahmad; Kartadie, Rikie (Universitas Negeri Semarang, 2018)
Abstract.Ã‚Â Improving the quality of learning is one of the basic, improvement of education as a whole. Efforts to improve the quality of education into an inteÃ‚Âgrated part of efforts to improve human quality, both aspects of ability, perÃ‚Âsonality, and responsibility. One to improve the quality of the learning process is by using an effective media, attract students to learn and explain thoroughly the material to be delivered so that in the end can improve student learning outcomes.The design of this research is Quasi-Experimental Design with Research model of Nonequivalent Pretest-Postest Control Group Design. The sample of the reÃ‚Âsearch are 60 students selected by Sample Random Sampling.Ã‚Â Data analysis was done with parametric statistic with the prerequisite test included a normality test, homogeneity test, then tested different and influence test.The result showed that the average score of the control group was 70.61, for the experimental group the average score was 74.81. There is the difference of result of student learning between the control group and experiment group after learning using visual media using Lectora application and result of influence test show result of t-count 3,621> t-table equal to 2,052 with it can be concluded that there the influence of learning result after given treatment.